IMPROVING STUDENTS' CREATIVE THINKING SKILLS WITH PROJECT BASED LEARNING - Faizah Wirta Putri Nasution; Nirwana Anas; Melfa Aisyah Hutasuhut (Universitas Negeri Padang, 2021)
This study aims to determine the effect of project-based learning (PBL) model on the creative thinking skills of class XI science students at MAN 1 Tapanuli Tengah on cell material. This research belongs to the type of quantitative descriptive research with data collection techniques are tests and non-tests that are carried out to measure students' creative thinking abilities. The sample in this study amounted to 2 classes, namely the experimental class and the control class. Data analysis used in the form of instrument calibration, data collection, data reduction, and data presentation. The results of Mann Whitney's hypothesis test on SPSS version 26 obtained a probability value (Asymp. Sig.) 0.116 < 0.05, Ho is accepted, meaning that there is no significant difference in each aspect of creative thinking ability between the control class and the experimental class. The results showed that the percentage of creative thinking ability of the experimental class was 60% and the control class was 50% with the criteria of moderate creative thinking ability. The conclusion in this study is that there is no significant effect of the application of project-based learning on students' creative thinking skills in cell material in class XI IPA MAN 1 Tapanuli Tengah.